Genetic diversity in maize at germination and seedling stages under simulated drought conditions - Mannan, Md Abdul; Begum, Ferdousi (Annals of Bangladesh Agriculture, 2023)
Ninety seven maize (Zea mays) genotypes were evaluated for germination and early seedling characters under PEG6000 (8%) induced drought stress to identify drought tolerant genotypes. Descriptive statistics for percentage of seed germination and abnormal seedling, shoot length, root length, and shoot dry weight, root dry weight, seedling length, seedling dry weight, and vigor index revealed significant variation among the genotypes studied. The percentage of germination and abnormal seedlings varied greatly among the genotypes. The first and second principal components (PC) of PCA results accounted for 73.15 and 26.85% of the total variation of maize genotypes, respectively. The first PC variation consisted primarily of relative seedling shoot dry weight and relative seedling root dry weight. Cluster analysis grouped the genotypes into four clusters. Cluster III genotypes performed better in terms of relative shoot dry weight, relative root dry weight, and number of abnormal seedlings, indicating drought tolerance. Very poorly performance was shown by genotypes in cluster IV, whereas moderately performance was shown by genotypes in cluster II and I. The clusters differed significantly from one another, according to D2 and multivariate analysis. Thirty six genotypes viz. BD-814, BD-810, BD-812, BD-821, BD-815, BD-10015, BD-10238, CML-552, BD-822, BD-826, CML-341, CML-555, CML-591, CML-523, CML-564, BD-817, BD-10018, BD-10240, CML-577, CML-342, CML-556, BD-837, CML-544, BD-827, BD-806, BD-835, BD-840, BD-842, BD-10010, CML-562, BD-10239, BD-10016, CML-593, CML-568 and BD-10234 demonstrated relatively drought tolerance during the germination and early seedling stages might be used in future breeding program. Ann. Bangladesh Agric. (2023) 27 (2): 19-30